Linking Public Spaces: Technical and Social Issues - Jancke, Gavin; Venolia, Gina; Grudin, Jonathan; Cadiz, J. J.; Gupta, Anoop (CHI '01: Proceedings of the SIGCHI conference on Human factors in computing systems, 2001)
Three public spaces frequency used by members of a single organization who are distributed across different floors of two buildings were linked by constantly-running video and audio connections. We discuss the design of the system, including issues in providing low-latency, full-duplex audio-video connectivity, ways to increase possibilities for interaction while addressing privacy concerns, and the introduction of the system to the community. We report on responses to the system and lessions learned, including unexpected issues, such as creative decorations of the spaces and assertions by a vocal minority of employees about the private nature of “public space.”